The effects of feeding with organic waste by terrestrial isopod Philoscia Muscorum on enzyme activities in an incubated soil - Sholpan S. Muminova; Gulsun Bayadilova; Oryngul Mukhametzhanova; Saule M. Seilgazina; Roza Zhumabayeva; Gulnissam Rvaidarova (Eurasian Journal of Soil Science, 2023)
Soil fauna are important biological factors that affect litter decomposition and play an important role in the release of nutrients and improve soil enzyme activities. This study focused on the effects of isopods on enzymatic activities of soil. Lab experiments were conducted to assess the influence of terrestrial isopod Philoscia Muscorum on enzyme activities during the incubation.In Lab experimental food sources from wheat straw were prepared. Dehydrogenase, urease, alkaline phosphatase and arylsulphatase activity in soil treated with different number of isopods with wheat straw were determined in 28 days incubation. Results showed that the presence of isopods significantly increased (P<0.05) enzymatic activities of soil except arylsulphatase compared with the control treatment. The findings demonstrate that the isopods could accelerate litter decomposition and improve soil dehydrogenase, urease and alkaline phosphatase activities in soil. This work provides evidence demonstrating that soil fauna can improve soil enzyme activity by promoting wheat straw decomposition.